2022
DOI: 10.3390/ijerph19052874
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Quality and Its Associations with Physical and Mental Health-Related Quality of Life among University Students: A Cross-Sectional Study

Abstract: The association between sleep problems and quality of life has been well documented and the COVID-19 pandemic seemingly had an impact on both sleep quality and health-related quality of life (HRQoL). However, recent evidence about this relationship among university students is limited. The aims of this study are to investigate the prevalence of poor sleep quality and insomnia and to explore the associations between these outcomes, perceived stress, and HRQoL among Italian university students. An anonymous ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 71 publications
11
23
0
Order By: Relevance
“…Therefore, whereas several studies conducted worldwide before the pandemic have already warned about university students’ risk of reporting stress-related negative health outcomes [ 14 , 15 , 16 ], the more updated research addressing the impact of COVID-19 emergency has underlined an even higher health risk reported by students globally [ 17 , 18 , 19 , 20 ]. In particular, research has highlighted that university students who perceived high levels of specific COVID-19-related stressors (i.e., stress related to changes in Relationships and Academic Life, Isolation, and Fear of Contagion) were at high risk for reporting several stress-related negative outcomes, such as cognitive impairment [ 21 ], psychophysical disorders [ 22 , 23 ] and poor mental health [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, whereas several studies conducted worldwide before the pandemic have already warned about university students’ risk of reporting stress-related negative health outcomes [ 14 , 15 , 16 ], the more updated research addressing the impact of COVID-19 emergency has underlined an even higher health risk reported by students globally [ 17 , 18 , 19 , 20 ]. In particular, research has highlighted that university students who perceived high levels of specific COVID-19-related stressors (i.e., stress related to changes in Relationships and Academic Life, Isolation, and Fear of Contagion) were at high risk for reporting several stress-related negative outcomes, such as cognitive impairment [ 21 ], psychophysical disorders [ 22 , 23 ] and poor mental health [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The study design was cross-sectional, and the research procedure was reported in detail previously [ 38 ]. Data were collected via an anonymous online survey delivered to students from Sapienza University of Rome through the Google Forms platform from March 2021 to June 2021.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Ban and Lee (2001) found that even when university students had sufficient sleep duration (i.e., objective), more than 30% of the sample reported having insufficient sleep (subjective). Further, subjective sleep quality has been associated with perceptions of quality of life, physical health and psychological health (Carpi et al, 2022;Putilov et al, 2021;Simor et al, 2015). Indeed, studies have identified a relationship between university students' subjective sleep quality and their emotional states (Ahammed et al, 2021;Arbinaga et al, 2018;Simor et al, 2015;Norbury & Evans, 2019).…”
Section: Practical Supportmentioning
confidence: 99%